In vitro rumen fermentation characteristics and microbes of thin tail sheep given sweet potato (Ipomoea batatas L) biomass - Asep Sudarman; M. Hayashida; M. Miralestari (Jurnal Ilmu Ternak dan Veteriner, 2016)
Sweet potato plant is produced in Indonesia in large quantities. Sweet potato leaves and stems can be used as a source of protein and the tuber can be used as an energy source. This study was aimed to analyze the effect of feeding of sweet potato biomass on the rumen fermentation characteristics, digestibility of dry matter and organic matter as well as rumen microbial population of thin tail sheep. This study used a randomized block design by applying four feed treatments, i.e., T0 (100% Napier grass), T1 (70% of Napier grass + 30% concentrate), T2 (50% of Napier grass + 50% sweet potato leaves), and T3 (70% sweet potato leaves + 30% sweet potato tuber) with three replicates. Rumen fluid samples were taken with stomach tube method using a vacuum pump.  Results showed that the T3 diet has higher (P<0.05) digestibility of dry matter and organic matter, concentration of NH3 and VFA, and rumen bacterial population than those of T0 and T1diets but similar to that of T2 diet. Rumen pH and protozoa population was not different among the treatments. It can be concluded that the use of sweet potato biomass can improve the quality of rumen fermentation of sheep.